2020
DOI: 10.2147/ndt.s268878
|View full text |Cite
|
Sign up to set email alerts
|

<p>Value of Combination of the A<sup>2</sup>DS<sup>2</sup> Score and IL-6 in Predicting Stroke-Associated Pneumonia</p>

Abstract: Purpose: To evaluate the value of the combination of the age, atrial fibrillation, dysphagia, male sex, and National Institutes of Health Stroke Scale (A 2 DS 2) score and serum interleukin 6 (IL-6) concentration in predicting stroke-associated pneumonia (SAP). Patients and Methods: A total of 398 patients with acute ischemic stroke (AIS) from the medical ward was included in this retrospective study. They were divided into the SAP group and non-SAP group according to the diagnostic criteria of SAP. Multivaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…First, it was the first study to explore the association between SAP and CSVD. Second, we also proposed models to predict the occurrence of SAP and the development of poor outcomes, continuing the findings of previous research (13,14,46), and improving the ability of clinical prediction. However, some limitations in our study should be noted.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…First, it was the first study to explore the association between SAP and CSVD. Second, we also proposed models to predict the occurrence of SAP and the development of poor outcomes, continuing the findings of previous research (13,14,46), and improving the ability of clinical prediction. However, some limitations in our study should be noted.…”
Section: Discussionsupporting
confidence: 53%
“…Previous studies had identified older age, atrial fibrillation, congestive heart failure, stroke severity, stroke subtype, and dysphagia, as important risk factors (10)(11)(12)(13), and established several SAP scales for early prediction, such as the A 2 DS 2 scale, the ISAN scale and the AIS-APS scale (6,12,14). The prediction efficiency of the A 2 DS 2 scale was better than others (15).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combination of serum albumin and body weight in GNRI may minimize the effects of confounding factors such as hydration status, which could better predict the adverse prognosis related to nutrition. Multiple biomarkers were associated with inflammation and showed the ability to predict outcomes or SAP events in stroke, such as CRP and IL‐6 (Lu et al., 2015 ; Yang et al., 2020 ). A study indicated that IL‐6 was related to SAP via activating the production of acute‐phase proteins and CRP in AIS (Yang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple biomarkers were associated with inflammation and showed the ability to predict outcomes or SAP events in stroke, such as CRP and IL‐6 (Lu et al., 2015 ; Yang et al., 2020 ). A study indicated that IL‐6 was related to SAP via activating the production of acute‐phase proteins and CRP in AIS (Yang et al., 2020 ). Besides, acute stroke may induce depression of the immune system with an elevated susceptibility to infections (Haeusler et al., 2008 ), which may be partly promoted by increased IL‐6, for the reason that IL‐6 plays a role in determining cellular immunity (Yang et al., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Stroke-associated pneumonia (SAP) often occurs after a stroke; approximately 7%–38% [ 3 8 ] of stroke patients are diagnosed with SAP during hospitalization. Once a patient develops SAP, it leads to a poor prognosis and a prolonged hospital duration [ 9 12 ].Early diagnosis and preventive treatment are necessary for patients at high risk of SAP. Therefore, an effective biomarker is needed for risk assessment and early detection of SAP.…”
Section: Introductionmentioning
confidence: 99%